Association between Alcohol Consumption and Body Composition in Russian Adults and Patients Treated for Alcohol-Related Disorders: The Know Your Heart Cross-Sectional Study - Nikita A. Mitkin; Tatiana N. Unguryanu; Sofia Malyutina; Alexander V. Kudryavtsev (International Journal of Environmental Research and Public Health, 2023)
There is conflicting evidence about the association between alcohol consumption and body composition (BC). We aimed to investigate this association in Russian adults. The study population included 2357 residents of Arkhangelsk aged 35–69 years, and 272 in-patients treated for alcohol problems (narcological patients) who participated in the Know Your Heart (KYH) cross-sectional study in 2015–2017. The participants were divided into five subgroups based on their alcohol use characteristics: non-drinkers, non-problem drinkers, hazardous drinkers, harmful drinkers, and narcological patients. Considering men, hazardous drinkers had a larger waist circumference (WC), waist-to-hip ratio (WHR), and percentage of body fat mass (%FM) compared to non-problem drinkers. In harmful drinking men, these differences were the opposite: a lower body mass index (BMI), hip circumference (HC), and %FM. Men among narcological patients had the lowest mean BMI, WC, HC, WHR, and %FM compared to other subgroups of men. As for women, non-drinkers had a lower BMI, WC, HC, and %FM compared to non-problem drinkers. Women among narcological patients had the lowest mean BMI and HC but an increased WHR compared to other subgroups of women. In conclusion, alcohol consumption levels had an inverted J-shaped association with adiposity-related BC parameters: they were elevated in hazardous drinkers but were reduced in harmful drinkers, and were even lower in patients with alcohol-related diagnoses.